A clonidina reduz a pressão arterial pulmonar em portadores de estenose mitral - Garcia, Maria Helena Domingues (2005)
Pulmonary circulation is a high flow, low resistance, and low pressure system. Several pathologies, including mitral stenosis, may elevate the impedance of this blood circuit and lead to a pulmonary arterial hypertension. Such syndrome is usually related to a high morbity and patient s death may occur because of the ischemic failure of right ventricle. The use of systemic vasodilating drugs to treat this syndrome is limited by the simultaneous systemic arterial hypotension they often produce. More selective agents to the pulmonary vasculature, such as synthetic analogs of prostacyclin, endothelin receptor inhibitors, and phosphodiesterase III inhibitors, have been choosen for medium and long-term treatment. Unfortunately, the most selective pulmonary hypotensive agent, the inhaled nitric oxide, which is used for short-term treatment, requires special and costly equipment for its administration, making it inaccessible to many hospitals. Furthermore, some degree of toxicity was associated with that substance. The lack of an ideal substance that simultaneously shows pulmonary selectivity, atoxicity, easy handling, accessibility and low cost, motivated the present study to test the effects of clonidine on pulmonary circulation. Clonidine is an alfa-2 adrenergic agonist. It promotes a systemic cardiocirculatory balance by modulating the adrenergic discharge at both central and peripheral levels. When used in clinical doses it presents no toxicity. Furthermore, it is easy to handle, accessible, and inexpensive. However, little has been reported about its pulmonary effect. Therefore, this work aimed to evaluate the effects of clonidine on the pulmonary arterial pressure, on the hemodynamics parameters concerned to the pulmonary circulatory system, as well as on the right ventricular function. At the same time, the action of clonidine on the systemic hemodynamics, cardiac rate, cardiac index and stroke index was also evaluated. This investigation took into account the degree of selectivity of this agent to the pulmonary vessels as well as the presence of a biphasic effect on the pulmonary arterial pressure. This effect has been largely reported on the vascular periferal system. The present research was performed as a prospective clinical trial developed on a group of 16 patients with pulmonary hypertension caused by mitral stenosis of rheumatic origin. Data were obtained before the anesthetic induction, but under the patient sedation. During the control phase, the variations of hemodynamic parameters under the action of a placebo were evaluated. During the test phase, the behavior of these parameters was evaluated under the clonidine effect. The time schedule for data measurements was the following: T0 (initial control); T1 (10 minutes after placebo administration); T2 (20 minutes after placebo administration); T3 (10 minutes after clonidine administration); T4 (20 minutes after clonidine administration). T2 was used as the control time to study the clonidine effects. Statistical analysis showed that during the control phase the variables remained unchanged, but under the effect of clonidine there was a significant reduction of the mean values concerned to the following parameters: pulmonary arterial mean pressure (27.1%) and systemic arterial mean pressure (20%), pulmonary vascular resistance index (34%) and systemic vascular resistance index (14.6%), right and left ventricular systolic work indexes (19.9% and 10%, respectively), right atrium pressure (11.5%), pulmonary arterial wedge pressure (21.5%), heart rate and cardiac index (15.8% and 7.9%, respectively). Besides that, a significant increase of the stroke index (10.2%) occured. The biphasic effect on the sistemic arterial pressure occured in 50% of the studied patients, whereas the same effect on the pulmonary arterial pressure was observed in 20% of the same sample. Clonidine also exerted a moderately selective action on the pulmonary circulation, demonstrated through the reduction of the relationship between mean value of the pulmonary vascular resistance index and mean value of the systemic vascular resistance index evaluated at the times T2 and T3.